BOOK REVIEWS (Journal of Finance, 1955)
Book reviewed in this article: Long‐Range Economic Projections . By C onference on R esearch in I ncome and W ealth The Future of Sterling . By A. C. L. D ay Survey of United States International Finance, 1953 . By G ardner P atterson , J ohn M. G unn , J r ., and D orothy L. S werdlove International Trade under Flexible Exchange Rates . By J ohn B urr W illiams The Intelligent Investor . By B enjamin G raham What about Mutual Funds? By J ohn A. S traley Monopoly and Competition in Banking . By D avid A. A lhadeff Business Fluctuations and Forecasting . By C arl A. D auten The Federal Reserve System, 1945–1949 . By J. S. F forde Montgomery's Federal Taxes . Edited by P hilip B ardes Private Credit and Public Debt . By A natol M urad Federal Debt‐Management Policies, 1865–1879 . By R obert T. P atterson The Theory of Fiscal Economics . By E arl R. R olph Robert Morris: Revolutionary Financier . By C larence L. V er S teeg Conference on Agricultural Taxation and Economic Development . By H askell P. W ald Taxation of the Forest Industries in Ontario . By G eorge C. W ilkes